Weakly $τ^\starα(σ_1,σ_2)$-continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of continuous multifunctions defined between an ideal topological space and a bitopological space, called upper weakly $τ^\starα(σ_1,σ_2)$-continuous multifunctions and lower weakly $τ^\starα(σ_1,σ_2)$-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper weakly$τ^\starα(σ_1,σ_2)$-continuous multifunctions and lower weakly $τ^\starα(σ_1,σ_2)$-continuous multifunctions are considered.
Keywords: upper weakly $τ^\starα(σ_1,σ_2)$-continuous multifunction; lower weakly $τ^\starα(σ_1,σ_2)$-continuous multifunction